Agricultural Practice Assessment to Accelerate Organic Rice Farming Adoption: A Case Study in West Java, Indonesia - Sujianto; Ermiati; Sudjarmoko Bedy (BIO Web of Conferences, 2023)
Rice is a crucial carbohydrate source for the world population’s food and global food security. The Indonesian government has tried to increase domestic production through the green revolution policy. The government has initiated concerns about enhancing rice quality through organic rice production. Organic rice has been emerging as an alternative to sustainable farming. Unfortunately, the acreage ratio to conventional farming is still relatively low, and productivity declined during the conversion period.This research aimed to explore deeply the agricultural practices between organic and conventional farming for fostering the adoption. That is why it is essential to be assessed comprehensively. This research focused on the organic rice farming production center in Subang and Tasikmalaya Regency, West Java Province. The total respondents were 203, consisting of 100 organic and 103 conventional smallholder farmers, respectively. Agricultural practice data of organic and conventional rice farming systemswere compared descriptively. Statistical analysis used Chi-square and t-test to test the significance of agricultural practices differences between the organic and conventional characteristics. The finding shows that organic rice farming had certain agricultural practices, such as farmers’ preferences to use variety, seedling, transplanting time, watering system, pest control, and fertilization approach. Organic farmers use a premium price-oriented variety, aromatic and red-rice types. Organic rice farmers produced their self-owned seed production. While in the cultivation technique, organic rice farming is considered to have more transplanting days, adopting alternate wetting and drying (AWD), using wide spacing at a minimum of 20x20 cm, and using an Integrated Pest Management (IPM) system.